Compromising on contradictory norms : a comparative analysis of differing United Nations responses to Kosovo and South Sudan - Bigej, Jarett Heath (My University, 2022)
COMPROMISING ON CONTRADICTORY NORMS: A COMPARATIVE ANALYSIS OF DIFFERING UNITED NATIONS RESPONSES TO KOSOVO AND SOUTH SUDAN What factors shaped the United Nations decision to grant membership to South Sudan but not to Kosovo? This study seeks to understand the role of the Security Council in recommending the membership of South Sudan to the United Nations but not Kosovo. As such, meetings, reports, and resolutions from the bodies of the United Nations will serve as primary source documentation, while the analytical framework will be supported by secondary source documentation like books and journal articles. In order to understand why South Sudan is now a sitting United Nations member while Kosovo is not, we must look at the factors that shaped this decision. This study examines how the following factors become effective in each case: great power politics, geopolitics, geo-economics, humanitarian interventionism, identity politics, and the legal framework. Process tracing helps to put these factors in context by guiding a number of observations through a historical and textual analysis. Then, by juxtaposing the distinct factors in each case it will become clear why Kosovo remains without United Nations membership.

ÇELİŞKİLİ NORMLAR ÜZERİNDE UZLAŞMAK: BM’NİN KOSOVA VE GÜNEY SUDAN’A FARKLILAŞAN YAKLAŞIMLARININ KARŞILAŞTIRMALI BİR ANALİZİ Birleşmiş Milletlerin Kosova’ya değil de Güney Sudan’a üyelik verme kararını hangi faktörler şekillendirdi? Bu çalışma, Kosova’nın değil de Güney Sudan’ın Birleşmiş Milletler üyeliğine tavsiye edilmesinde Güvenlik Konseyi’nin rolünü anlamaya çalışmaktadır. Bu nedenle, Birleşmiş Milletler organlarından alınan toplantılar, raporlar ve kararlar birincil kaynak görevi görecek olup analitik çerçeve de kitap ve makaleler gibi ikincil kaynaklarla desteklenecektir. Neden Güney Sudan’ın Birleşmiş Milletler üyesi olup Kosova’nın olamadığını anlamak için bu kararı şekillendiren faktörlere bakmamız gerekmektedir. Bu çalışma şu faktörlerin her iki durumda da nasıl etkili olduğunu incelemektedir: Büyük Güç Siyaseti, jeopolitik, jeo-ekonomi, insani müdahale, kimlik siyaseti ve yasal çerçeve. Süreç izleme yöntemi, tarihsel ve metinsel bir analiz yoluyla bir dizi gözlemi yönlendirerek bu faktörleri bir bağlama oturtmaya yardımcı olmaktadır. Bu durumda, her durumdaki farklı faktörleri bir araya getirmek Kosova’nın neden hala Birleşmiş Milletler üyeliğine sahip olamadığını açıklığa kavuşturacaktır.
Keywords: BM Üyeliği; Büyük Güç Siyaseti; Geopolitics; Great Power Politics; Güney Sudan; Identity Politics; International relations; Jeopolitik; Kimlik Siyaseti Kosovo; Kosova; Kosova (Sırbistan); Kosovo (Serbia); Recognition; South Sudan; Sudan; Tanınma; Uluslararası ilişkiler; UN Membership